USM-FAU COLLABORATION TO ENSURE SUCCESS IN DIVERSITY EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 September 2016 Universiti Sains Malaysia (USM) continues to expand its international collaborative efforts when its School of Educational Studies hosted the USMFAU Conference 2016 with FriedrichAlexander Universitat (FAU), ErlangenNurnberg, Germany.